A PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, its preparation method and application
Patent Information
- Application Number
- CN202611101794.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明的目的在于提供一种PVDF&PDA界面改性碳纤维增强树脂基摩擦材料及其制备方法与应用,解决现有树脂基摩擦材料阻尼性能、耐磨性能及摩擦稳定性难以同步提高的问题
本发明提供一种PVDF&PDA界面改性碳纤维增强树脂基摩擦材料,包含10~20%的热固性酚醛树脂、15~25%的PVDF&PDA双涂层改性碳纤维和55~75%的填料,由碳纤维、PDA过渡层、PVDF功能层和树脂基体组成的梯度界面体系。其中,PDA层凭借其优异的粘附性能和表面活性,在碳纤维与PVDF之间形成稳定的桥接层,有效增强界面粘附力并提高界面剪切强度和载荷传递效率;而PVDF层作为粘弹性聚合物,在摩擦或冲击载荷下可通过界面剪切变形和链段运动实现能量耗散,同时梯度界面结构能够缓解弹性模量突变、降低应力集中并抑制界面裂纹萌生与扩展。两者协同作用使得该摩擦材料在保证界面强度的同时,损耗因子达到0.01798~0.01902,磨损率低至1.63~2.52×10-8cm3/J,且噪声水平下降了10.578~15.345 dB(A),实现了力学性能、阻尼性能和耐磨性能的综合优化,尤其适用于对减振降噪和服役稳定性要求较高的摩擦制动场景。
Smart Images

Figure CN122958818A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of friction materials and carbon fiber interface modification technology, and relates to a PVDF & PDA interface modified carbon fiber reinforced resin-based friction material, its preparation method and application. Background Technology
[0002] Resin-based friction materials are widely used in braking systems of automobiles, rail transportation, and engineering machinery due to their low density, stable frictional performance, mature manufacturing processes, and high designability. As braking systems evolve towards higher speeds, heavier loads, and greater comfort, the vibration, noise, and wear problems generated during friction braking are becoming increasingly prominent, placing higher demands on the damping performance, wear resistance, and mating-component friendliness of friction materials. Damping technology is one of the most effective means of suppressing vibration and noise in engineering; materials dissipate vibration energy through energy conversion and transfer using their inherent properties. In existing technologies, viscoelastic polymers are often introduced into the resin matrix to improve the damping performance of friction materials. However, this method easily leads to microphase separation within the matrix, weakening the material's mechanical properties. It often comes at the cost of sacrificing the matrix's heat resistance and structural stability, making it difficult to simultaneously improve both damping and wear resistance.
[0003] Carbon fiber, with its high strength, high modulus, and good heat resistance, is often introduced as a reinforcing phase into resin-based friction materials to improve their mechanical properties and structural stability. However, the strong chemical inertness of carbon fiber surfaces leads to poor interfacial compatibility with the resin matrix. Under frictional and thermal loads, microcracks, debonding, and fiber pull-out can easily occur in the interfacial region, resulting in reduced stress transmission efficiency, accelerated material wear, and potentially inducing frictional vibration and noise problems. The interfacial layer, as a crucial component of fiber-reinforced composites, plays a key role in load transmission and energy dissipation. For resin-based friction materials, a well-designed fiber / matrix interfacial structure can effectively utilize the deformation energy dissipation capacity of viscoelastic polymers, thereby improving the material's damping performance.
[0004] In contrast, constructing a viscoelastic polymer interfacial coating on the fiber surface can localize the damping phase in the fiber / matrix interface region, causing interfacial shear deformation under frictional loads, thereby effectively dissipating vibrational energy and helping to alleviate interfacial stress concentration. However, existing interfacial coating modification methods mostly focus on improving interfacial bonding strength, neglecting the viscoelastic characteristics of the coating material and its synergistic energy dissipation effect during friction. Furthermore, some coatings have limited bonding stability with the fiber or matrix, making them prone to peeling or wear during service, affecting the overall material performance. Therefore, while ensuring interfacial bonding, it is urgent to explore interfacial coating modification schemes with good viscoelasticity and wear resistance to achieve a comprehensive improvement in the damping performance, wear resistance, and frictional stability of resin-based friction materials. Summary of the Invention
[0005] The purpose of this invention is to provide a PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, its preparation method and application, to solve the problem that the damping performance, wear resistance and friction stability of existing resin-based friction materials are difficult to improve simultaneously.
[0006] To achieve the above objectives, the present invention employs the following technical solution: A PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material comprises, by weight percentage: 10-20% thermosetting phenolic resin, 15-25% PVDF & PDA double-coated modified carbon fiber, and 55-75% filler.
[0007] Furthermore, thermosetting phenolic resins include boron-modified phenolic resins, cashew nut shell oil-modified phenolic resins, nitrile-modified phenolic resins, and oil-modified phenolic resins. PVDF&PDA double-coated modified carbon fibers include polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, and viscose-based carbon fibers modified with PVDF&PDA double coating. The filler is one or more of the following: alumina, barium sulfate, chromite, calcium carbonate, carbon black, graphite, fluorite powder, and kaolin.
[0008] A method for preparing the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material includes: The pretreated carbon fiber was immersed in hydrogen peroxide solution for oxidation treatment, and then washed with deionized water, filtered and dried to obtain oxidized carbon fiber. Dilute hydrochloric acid solution was added dropwise to an aqueous solution of tris(hydroxymethyl)aminomethane to adjust the pH, resulting in a Tris-HCl buffer solution. Dopamine was then added to the Tris-HCl buffer solution to obtain an aqueous solution of DA. Oxidized carbon fibers were immersed in a DA aqueous solution to undergo a self-polymerization reaction. After washing with deionized water, filtering, and drying, PDA single-coated modified carbon fibers were obtained. Polyvinylidene fluoride was added to 1-methyl-2-pyrrolidone organic solvent and dissolved completely under heating and stirring conditions to obtain a PVDF solution. PDA-coated modified carbon fiber is immersed in PVDF solution for coating, so that PVDF forms a coating layer on the surface of the carbon fiber. After washing with deionized water, filtering and drying, PVDF&PDA double-coated modified carbon fiber is obtained. Thermosetting phenolic resin, PVDF & PDA double-coated modified carbon fiber and filler are mixed, filled into a mold, and then subjected to hot pressing curing and heat treatment to obtain PVDF & PDA interface modified carbon fiber reinforced resin-based friction material.
[0009] Furthermore, the pretreatment process for carbon fiber is as follows: Soak carbon fibers in acetone for 24-48 hours, wash thoroughly with deionized water and dry at 80-100℃ for 4-6 hours.
[0010] Furthermore, the mass fraction of the hydrogen peroxide solution is 25%~35%; The mass-to-volume ratio of the pretreated carbon fiber to the hydrogen peroxide solution is 1:20~30; The oxidation treatment time is 20~28h.
[0011] Furthermore, the pH of the Tris-HCl buffer solution is 8.5; The mass concentration of tris(hydroxymethyl)aminomethane aqueous solution is 1~2 g / L; The concentration of the dilute hydrochloric acid solution is 0.01~0.02 mmol / L; The mass concentration of dopamine aqueous solution is 3~4 g / L; The mass-to-volume ratio of oxidized carbon fiber to DA aqueous solution is 1:100~120; The self-polymerization reaction time is 24~36h, and the temperature is room temperature.
[0012] Furthermore, the mass ratio of polyvinylidene fluoride to 1-methyl-2-pyrrolidone is 1:19~39; The heating temperature is 80~100℃; The stirring speed is 800~1000 r / min, and the stirring time is 10~15 min; The mass ratio of PDA single-coated modified carbon fiber to PVDF solution is 1:20~30; The coating time is 3-4 hours, and the temperature is 80-100℃.
[0013] Furthermore, the drying temperature of the oxidized carbon fiber, the PDA single-coated modified carbon fiber, and the PVDF&PDA interface modified carbon fiber were all 60~80℃, and the drying time was all 6~12h.
[0014] Furthermore, the hot-press curing treatment is performed at a pressure of 5~10MPa, a temperature of 160~185℃, and a time of 10~15min; The heat treatment pressure is 1~2 MPa, and the gradient heating process is as follows: heat to 110~120℃ and hold for 30~40 min, heat to 130~140℃ and hold for 65~75 min, heat to 150~160℃ and hold for 120~140 min, heat to 170~180℃ and hold for 45~55 min, and then cool to room temperature.
[0015] Application of the PVDF & PDA interface modified carbon fiber reinforced resin-based friction material in friction braking devices.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, comprising 10-20% thermosetting phenolic resin, 15-25% PVDF & PDA double-coated modified carbon fiber, and 55-75% filler, forming a gradient interface system composed of carbon fiber, a PDA transition layer, a PVDF functional layer, and a resin matrix. The PDA layer, with its excellent adhesion and surface activity, forms a stable bridging layer between the carbon fiber and PVDF, effectively enhancing interfacial adhesion and improving interfacial shear strength and load transfer efficiency. The PVDF layer, as a viscoelastic polymer, dissipates energy under friction or impact loads through interfacial shear deformation and chain segment movement. Simultaneously, the gradient interface structure alleviates abrupt changes in elastic modulus, reduces stress concentration, and inhibits the initiation and propagation of interfacial cracks. The synergistic effect of these two components enables the friction material to maintain interfacial strength while achieving a loss factor of 0.01798-0.01902 and a wear rate as low as 1.63-2.52 × 10⁻⁶. -8 cm 3 / J, and the noise level decreased by 10.578~15.345 dB(A), achieving comprehensive optimization of mechanical performance, damping performance and wear resistance performance, and is especially suitable for friction braking scenarios with high requirements for vibration reduction, noise reduction and service stability.
[0017] This invention also provides a method for preparing a PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material. Through organic solvent cleaning, hydrogen peroxide oxidation, and dopamine self-polymerization under weakly alkaline conditions, a PDA underlayer coating is successively constructed on the carbon fiber surface. Utilizing its excellent adhesion properties and surface activity, a stable bridging layer is formed between the carbon fiber and PVDF. Subsequently, a PVDF coating is impregnated to enhance the bonding stability between the PVDF coating and the fiber matrix, resulting in a PVDF and PDA dual-coated modified carbon fiber. This gradient interface is beneficial for improving the interfacial contact state between the fiber and the resin matrix, enhancing interfacial bonding force, and improving load transfer efficiency, thereby improving the overall mechanical properties of the composite material. The modified carbon fiber is then mixed with phenolic resin and fillers and hot-pressed to prepare the modified friction material. Polyvinylidene fluoride (PVDF) is a viscoelastic polymer with excellent chemical stability, good mechanical properties, and wear resistance. It can undergo plastic deformation during friction, which is beneficial for energy dissipation. Polydopamine (PDA) is a biomimetic polymer with strong adhesion and surface activity, and can be deposited in situ on the surfaces of various materials, providing an effective way to construct functionalized interfacial coatings. This invention's interface modification method employs solution impregnation and conventional hot-pressing molding processes. The process steps are clearly defined, parameters are highly adjustable, and it is easily integrated with existing resin-based friction material production processes. The prepared double-coated modified carbon fiber fully leverages the advantages of interface modification. The polymer coating enhances the coating's deformability, simultaneously improving damping performance and interfacial bonding, effectively reducing friction material wear and suppressing vibration and noise. Throughout the preparation process, no strong acids or alkalis are used to corrode the carbon fiber, avoiding damage to the fiber structure and equipment corrosion risks. This helps maintain the original mechanical properties of the carbon fiber while improving process safety and environmental friendliness. The friction material prepared by this invention exhibits excellent wear resistance and vibration reduction properties, making it suitable for friction braking components in automobiles, rail transportation, engineering machinery, and industrial transmissions, especially suitable for applications requiring high vibration and noise reduction performance, wear resistance, and service stability.
[0018] Furthermore, the precise limitation of acetone soaking time (24-48h), drying temperature (80-100℃), and drying time (4-6h) in the carbon fiber pretreatment process ensures that organic sizing agents and contaminants on the carbon fiber surface are fully dissolved and removed. At the same time, the mild drying conditions prevent the fiber from being damaged by high-temperature oxidation, providing a clean and uniform surface-activated substrate for subsequent oxidation treatment. This effectively ensures the uniform deposition and firm adhesion of the PDA coating on the carbon fiber surface, improving the stability and repeatability of interface modification from the source.
[0019] Furthermore, the optimization of hydrogen peroxide concentration (25%~35%), feed-to-liquid ratio (1:20~30), and treatment time (20~28h) during oxidation treatment, as well as the precise control of buffer pH (8.5), dopamine concentration (3~4g / L), reaction time, and temperature (room temperature, 24~36h) during dopamine self-polymerization, provides an optimal process window for the introduction of surface active groups on carbon fibers and the control of the thickness and morphology of the PDA coating. These parameters work synergistically to ensure sufficient surface active sites to enhance the adhesion of the subsequent PVDF coating, while avoiding excessive oxidation or excessive coating thickness that could negatively impact the fiber strength, thus maximizing the functionality of the gradient interface structure.
[0020] Furthermore, by limiting the mass ratio of PVDF to 1-methyl-2-pyrrolidone (1:19~39), the heating temperature (80~100℃), and the stirring speed and time (800~1000r / min, 10~15min), the viscosity and uniformity of the PVDF solution were effectively controlled. This ensured that the PDA single-coated modified carbon fiber could obtain a continuous, dense, and appropriately thick PVDF outer coating during the impregnation and coating process (mass ratio 1:20~30, temperature 80~100℃, time 3~4h). This process window not only ensured that the PVDF functional layer could undergo sufficient plastic deformation to dissipate energy during friction, but also avoided the risk of increased interfacial brittleness or detachment caused by excessive coating thickness, thus achieving a good balance between coating efficiency and coating quality.
[0021] Furthermore, the oxidized carbon fibers, PDA single-coated modified carbon fibers, and the final PVDF & PDA double-coated modified carbon fibers were all dried at 60-80℃ for 6-12 hours, providing mild and sufficient heat treatment conditions. This effectively removed residual moisture or organic solvents introduced at each stage, while avoiding damage to the chemical structure and physical morphology of the PDA active layer and PVDF functional layer caused by high-temperature drying. This ensured the structural integrity and stability between the coating interfaces, laying the foundation for good integration of the gradient interface with the resin matrix during subsequent hot pressing.
[0022] Furthermore, by controlling the pressure (5~10MPa), temperature (160~185℃), and time (10~15min) during the hot-pressing curing stage, and combining this with a gradient heating process during the heat treatment stage, the full cross-linking reaction of the phenolic resin during the curing process is effectively ensured. At the same time, the gradient heating method significantly alleviates the thermal stress and shrinkage stress caused by rapid temperature changes inside the product, avoiding interface debonding or the generation of internal microcracks. This ensures the compactness of the internal structure of the friction material and the reliability of the interfacial bonding between the fiber, coating, and resin components, ultimately giving the product stable and excellent mechanical and tribological properties.
[0023] This invention also provides an application of PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material in friction braking devices. It fully utilizes the low wear rate, high damping loss factor, and significant noise reduction characteristics of PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, making it particularly suitable for braking components in the automotive, rail transportation, construction machinery, and industrial transmission fields where high vibration and noise reduction, wear resistance, and service stability are required. Transforming the microscopic structural advantages of the material into macroscopic application effectiveness not only broadens the application scope of high-performance polymer-based friction materials in high-end equipment manufacturing but also provides a practical and effective technical solution to address industry pain points such as high-frequency screeching and excessively rapid wear in traditional braking devices. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a SEM image of the carbon fiber pretreated in step 1 of Comparative Example 1 of the present invention.
[0026] Figure 2 The image shows the morphology of CF@PVDF in step 4 of Comparative Example 2 of the present invention, where (a) is a SEM image of CF@PVDF and (b) is a distribution map of F element.
[0027] Figure 3 The image shows the morphology of the CF@PDA in step 4 of Embodiment 1 of the present invention, where (a) is a SEM image of the CF@PDA and (b) is a map of the N element distribution.
[0028] Figure 4 The image shows the morphology of CF@PVDF&PDA in step 6 of embodiment 1 of the present invention, wherein (a) is a SEM image of CF@PVDF&PDA, (b) is a distribution map of N element, and (c) is a distribution map of F element.
[0029] Figure 5 The Fourier transform infrared (FTIR) spectra of the modified carbon fiber prepared in Example 1 of the present invention and the carbon fibers prepared in Comparative Examples 1 and 2 are shown. CF is the FTIR spectrum of the carbon fiber obtained in step 1 of Comparative Example 1, CF@PVDF is the FTIR spectrum of the modified carbon fiber obtained in step 4 of Comparative Example 2, and CF@PVDF&PDA is the FTIR spectrum of the modified carbon fiber obtained in step 6 of Example 1.
[0030] Figure 6The diagram shows the dynamic friction coefficients of the PVDF & PDA interface-modified carbon fiber reinforced resin-based friction materials prepared according to the present invention under 300 consecutive braking cycles. Specifically, S-CF0 represents the dynamic friction coefficient of the unmodified carbon fiber reinforced resin-based friction material prepared in Comparative Example 1 under 300 consecutive braking cycles, S-CF@PVDF represents the dynamic friction coefficient of the PVDF single-coat modified carbon fiber reinforced resin-based friction material prepared in Comparative Example 2 under 300 consecutive braking cycles, and S-CF@PVDF&PDA represents the dynamic friction coefficient of the PVDF & PDA double-coat modified carbon fiber reinforced resin-based friction material prepared in Example 1 under 300 consecutive braking cycles.
[0031] Figure 7 The figures show a comparison of the wear rates of the PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material and its counterpart prepared according to the present invention. Specifically, S-CF0 is a comparison of the wear rates of the unmodified carbon fiber reinforced resin-based friction material and its counterpart prepared in Comparative Example 1; S-CF@PVDF is a comparison of the wear rates of the PVDF single-coat modified carbon fiber reinforced resin-based friction material and its counterpart prepared in Comparative Example 2; and S-CF@PVDF&PDA is a comparison of the wear rates of the PVDF & PDA double-coat modified carbon fiber reinforced resin-based friction material and its counterpart prepared in Example 1. Detailed Implementation
[0032] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0033] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0034] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0035] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0036] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0037] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0038] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0039] The present invention will now be described in further detail with reference to the accompanying drawings: This invention provides a PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, which, by mass percentage, comprises 10-20% thermosetting phenolic resin, 15-25% PVDF & PDA double-coated modified carbon fiber, and 55-75% filler.
[0040] The thermosetting phenolic resin includes boron-modified phenolic resin, cashew nut shell oil-modified phenolic resin, nitrile-modified phenolic resin, and oil-modified phenolic resin. Preferably, the particle size of the thermosetting phenolic resin is 200 mesh.
[0041] PVDF & PDA double-coated modified carbon fibers include PVDF & PDA double-coated modified polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, and viscose-based carbon fibers; wherein the diameter of the carbon fibers is 6~10µm and the length is 6~10mm.
[0042] The filler is one or more of the following: alumina, barium sulfate, calcium sulfate, chromite, calcium carbonate, carbon black, graphite, fluorite powder, and kaolin. Preferably, the filler particle size is 100-200 mesh.
[0043] This invention also provides a method for preparing a PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, specifically including the following steps: Step 1: Pre-treat the carbon fiber by soaking it in acetone for 24-48 hours to remove the sizing agent and impurities from the surface of the carbon fiber. Then, wash it thoroughly with deionized water and dry it at a temperature of 80-100℃ for 4-6 hours to obtain pre-treated carbon fiber (CF).
[0044] Step 2: Prepare a hydrogen peroxide solution with a mass fraction of 25%~35%, immerse the pretreated carbon fiber in the hydrogen peroxide solution for oxidation for 20~28 hours to increase the grooves on the fiber surface, thereby facilitating coating adhesion. After washing with deionized water, filtering and drying, the oxidized carbon fiber is obtained.
[0045] Step 3: Add tris(hydroxymethyl)aminomethane (Tris) to deionized water, then add dilute hydrochloric acid solution dropwise to adjust the pH to 8.5 to obtain a Tris-HCl buffer solution. Add dopamine (DA) to the Tris-HCl buffer solution to obtain a DA aqueous solution.
[0046] Step 4: Immerse the oxidized carbon fiber in a DA aqueous solution. PDA is formed on the surface of the carbon fiber through the DA self-polymerization reaction. After washing with deionized water, filtering and drying, PDA single-coated modified carbon fiber (CF@PDA) is obtained.
[0047] Step 5: Add PVDF to 1-methyl-2-pyrrolidone (NMP) organic solvent, and under heating and stirring conditions, allow PVDF to dissolve completely to obtain a PVDF solution.
[0048] Step 6: Immerse CF@PDA in PVDF solution to form a coating layer of PVDF on the carbon fiber surface. Then squeeze out the excess solution, wash with deionized water, filter and dry to obtain PVDF&PDA double-coated modified carbon fiber (CF@PVDF&PDA).
[0049] Step 7: Weigh the thermosetting phenolic resin, PVDF&PDA double-coated modified carbon fiber (CF@PVDF&PDA), and filler according to the specified ratio, and mix them at high speed to obtain a mixed powder. The mixed powder should have a density of 1.8 g / cm³. 3 After being filled into a mold and subjected to hot pressing curing and heat treatment processes, PVDF & PDA interface modified carbon fiber reinforced resin-based friction material is obtained.
[0050] Preferably, in step two, the mass-to-volume ratio of the pretreated carbon fiber to the hydrogen peroxide solution is 1:20~30.
[0051] Preferably, in step three, the mass concentration of Tris is 1~2 g / L, the concentration of the dilute hydrochloric acid solution is 0.01~0.02 mmol / L, the mass concentration of the DA aqueous solution is 3~4 g / L, the time for DA to self-polymerize on the carbon fiber surface to form PDA is 24~36 h, and the temperature is room temperature.
[0052] Preferably, in step five, the mass ratio of PVDF to NMP in the PVDF solution is 1:19~39, the temperature is 80~100℃, the rotation speed is 800~1000r / min, and the time is 10~15min.
[0053] Preferably, in step six, the mass ratio of CF@PDA to PVDF solution is 1:20~30, the time is 3~4 hours, and the temperature is 80~100℃.
[0054] Preferably, in step six, the mass-to-volume ratio of the oxidized carbon fiber to the DA aqueous solution is 1:100~120.
[0055] Preferably, in steps two, four, and six, the drying temperature of the oxidized carbon fiber, CF@PDA, and CF@PVDF&PDA is 60~80℃, and the drying time is 6~12h.
[0056] Preferably, in step seven, the high-speed stirring process involves a rotation speed of 10,000 to 12,000 rpm and a stirring time of 10 to 15 seconds.
[0057] Preferably, in step seven, the hot-press curing process has a pressure of 5~10MPa, a temperature of 160~185℃, and a time of 10~15min; the heat treatment process has a pressure of 1~2MPa, adopts a gradient heating program, heats to 110~120℃ and holds for 30~40min, heats to 130~140℃ and holds for 65~75min, heats to 150~160℃ and holds for 120~140min, heats to 170~180℃ and holds for 45~55min, and then cools to room temperature.
[0058] This invention also provides an application of the above-mentioned PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material in friction braking devices. The prepared PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material exhibits excellent damping characteristics and wear resistance. During friction braking, it can effectively improve load transmission, alleviate interface stress concentration, and inhibit interface debonding and fiber pull-out behavior, thus reducing vibration and noise levels and improving stability and durability. Therefore, it is suitable for braking systems and industrial friction transmission components in automobiles, construction machinery, and other fields where high vibration reduction, noise reduction, and wear resistance are required.
[0059] The present invention will be further described in detail below through specific embodiments: Example 1: Step 1: Pre-treat polyacrylonitrile-based carbon fibers by soaking the carbon fibers in acetone for 48 hours, washing them thoroughly with deionized water, and drying them at 80°C for 6 hours to obtain pre-treated carbon fibers. Step 2: Prepare 500 mL of 30% hydrogen peroxide solution, immerse 20 g of pretreated carbon fiber in the hydrogen peroxide solution for oxidation for 24 h, wash and filter with deionized water, and dry at 60 °C for 12 h to obtain oxidized carbon fiber. Step 3: Add 3g Tris to 2L of deionized water, then add 0.015mmol / L dilute hydrochloric acid solution dropwise to the aqueous solution to adjust the pH to 8.5, thus obtaining a Tris-HCl buffer solution. Add 7g DA to the Tris-HCl buffer solution to obtain a DA aqueous solution. Step 4: Immerse 20g of oxidized carbon fiber in DA aqueous solution and allow it to self-polymerize at room temperature for 30h. After washing and filtering with deionized water, dry at 80℃ for 6h to obtain CF@PDA. Step 5: Add 20g of PVDF to 480g of NMP organic solvent, and stir at 85℃ and 950rpm for 12min to fully dissolve the PVDF and obtain a PVDF solution. Step 6: Immerse 20g of CF@PDA in PVDF solution and treat at 85℃ for 3.5h. Then squeeze out the excess solution, wash with deionized water, filter, and dry at 70℃ for 8h to obtain CF@PVDF&PDA. Step 7: Accurately weigh 15g of cashew nut shell oil modified phenolic resin, 20g of CF@PVDF&PDA, 15g of calcium sulfate, 5g of alumina, 10g of barium sulfate, 10g of chromite, 1g of carbon black, and 24g of calcium carbonate. Stir the above raw materials at 10000 rpm for 15 seconds to obtain a mixed powder. Adjust the density of the mixed powder to 1.8g / cm³. 3 Fill the mold; Step 8: Place the mold filled with the mixed powder into a flat vulcanizing machine for hot pressing and curing at a pressure of 5.5 MPa, a temperature of 165°C, and a time of 13 min to obtain a pre-cured friction material. Apply a pressure of 1.5 MPa to the pre-cured friction material using a fixture and place it in an oven for heat treatment. Hold at 115°C for 35 min, 135°C for 70 min, 155°C for 130 min, and 175°C for 50 min. Then cool to room temperature to obtain a PVDF & PDA interface modified carbon fiber reinforced resin-based friction material.
[0060] Example 2: Step 1: Pre-treat polyacrylonitrile-based carbon fibers by soaking the carbon fibers in acetone for 24 hours, washing them thoroughly with deionized water, and drying them at 90°C for 5 hours to obtain pre-treated carbon fibers. Step 2: Prepare 500 mL of 25% hydrogen peroxide solution, immerse 25 g of pretreated carbon fiber in the hydrogen peroxide solution for oxidation for 28 h, wash and filter with deionized water, and dry at 70 °C for 10 h to obtain oxidized carbon fiber. Step 3: Add 2.75g Tris to 2.75L of deionized water, then add 0.01mmol / L dilute hydrochloric acid solution dropwise to the aqueous solution to adjust the pH to 8.5, thus obtaining a Tris-HCl buffer solution. Add 8.25g DA to the Tris-HCl buffer solution to obtain an aqueous solution of DA. Step 4: Immerse 25g of oxidized carbon fiber in DA aqueous solution and allow it to self-polymerize at room temperature for 24h. After washing and filtering with deionized water, dry at 70℃ for 10h to obtain CF@PDA. Step 5: Add 18.75g of PVDF to 731.25g of NMP organic solvent, and stir at 80℃ and 1000rpm for 15min to fully dissolve the PVDF and obtain a PVDF solution. Step 6: Immerse 25g of CF@PDA in PVDF solution and treat at 80℃ for 4h. Then squeeze out the excess solution, wash with deionized water, filter, and dry at 80℃ for 6h to obtain CF@PVDF&PDA. Step 7: Accurately weigh 20g boron-modified phenolic resin, 25g CF@PVDF&PDA, 10g calcium sulfate, 5g chromite, 5g alumina, 10g fluorite powder, 1g carbon black, and 24g calcium carbonate. Stir the above raw materials at 12000rpm for 10s to obtain a mixed powder. Adjust the density of the mixed powder to 1.8g / cm³. 3 Fill the mold; Step 8: Place the mold filled with the mixed powder into a flat vulcanizing machine for hot pressing and curing at a pressure of 6.5 MPa, a temperature of 160°C, and a time of 10 min to obtain a pre-cured friction material. Apply a pressure of 1 MPa to the pre-cured friction material using a fixture and place it in an oven for heat treatment. Hold at 120°C for 30 min, 140°C for 65 min, 160°C for 120 min, and 180°C for 45 min. Then cool to room temperature to obtain a PVDF & PDA interface modified carbon fiber reinforced resin-based friction material.
[0061] Example 3: Step 1: Pre-treat the pitch-based carbon fiber by soaking the carbon fiber in acetone for 48 hours, washing it thoroughly with deionized water, and drying it at 80°C for 6 hours to obtain the pre-treated carbon fiber. Step 2: Prepare 500 mL of 30% hydrogen peroxide solution, immerse 20 g of pretreated carbon fiber in the hydrogen peroxide solution for oxidation for 24 h, wash and filter with deionized water, and dry at 80 °C for 6 h to obtain oxidized carbon fiber. Step 3: Add 3.3g Tris to 2.2L of deionized water, then add 0.015mmol / L dilute hydrochloric acid solution dropwise to the aqueous solution to adjust the pH to 8.5, thus obtaining a Tris-HCl buffer solution. Add 7.7g DA to the Tris-HCl buffer solution to obtain a DA aqueous solution. Step 4: Immerse 20g of oxidized carbon fiber in DA aqueous solution and allow it to self-polymerize at room temperature for 30h. After washing and filtering with deionized water, dry at 80℃ for 6h to obtain CF@PDA. Step 5: Add 25g of PVDF to 475g of NMP organic solvent, and stir at 90℃ and 900rpm for 12min to fully dissolve the PVDF and obtain a PVDF solution. Step 6: Immerse 20g of CF@PDA in PVDF solution and treat at 90℃ for 3.5h. Then squeeze out the excess solution, wash with deionized water, filter, and dry at 70℃ for 8h to obtain CF@PVDF&PDA. Step 7: Accurately weigh 15g of oil-modified phenolic resin, 20g of CF@PVDF&PDA, 15g of calcium sulfate, 5g of alumina, 10g of barium sulfate, 10g of chromite, 1g of carbon black, and 24g of calcium carbonate. Stir the above raw materials at 11000rpm for 12s to obtain a mixed powder. Adjust the density of the mixed powder to 1.8g / cm³. 3 Fill the mold; Step 8: Place the mold filled with the mixed powder into a flat vulcanizing machine for hot pressing and curing at a pressure of 5.5 MPa, a temperature of 165°C, and a time of 13 min to obtain a pre-cured friction material. Apply a pressure of 1.5 MPa to the pre-cured friction material using a fixture and place it in an oven for heat treatment. Hold at 115°C for 35 min, 135°C for 70 min, 155°C for 130 min, and 175°C for 50 min. Then cool to room temperature to obtain a PVDF interface-modified carbon fiber reinforced resin-based friction material.
[0062] Example 4: Step 1: Pre-treat the viscose-based carbon fiber by soaking the carbon fiber in acetone for 36 hours, washing it thoroughly with deionized water, and drying it at 100°C for 4 hours to obtain the pre-treated carbon fiber. Step 2: Prepare 450 mL of 35% hydrogen peroxide solution, immerse 15 g of pretreated carbon fiber in the hydrogen peroxide solution for oxidation for 20 h, wash and filter with deionized water, and dry at 80 °C for 6 h to obtain oxidized carbon fiber. Step 3: Add 3.6g Tris to 1.8L of deionized water, then add 0.02mmol / L dilute hydrochloric acid solution dropwise to the aqueous solution to adjust the pH to 8.5, thus obtaining a Tris-HCl buffer solution. Add 7.2g DA to the Tris-HCl buffer solution to obtain a DA aqueous solution. Step 4: Immerse 15g of oxidized carbon fiber in DA aqueous solution and allow it to self-polymerize at room temperature for 36h. After washing and filtering with deionized water, dry at 80℃ for 6h to obtain CF@PDA. Step 5: Add 15g of PVDF to 285g of NMP organic solvent, and stir at 100℃ and 800rpm for 10min to fully dissolve the PVDF and obtain a PVDF solution. Step 6: Immerse 15g of CF@PDA in PVDF solution and treat at 100℃ for 3h. Then squeeze out the excess solution, wash with deionized water, filter, and dry at 70℃ for 8h to obtain CF@PVDF&PDA. Step 7: Accurately weigh 10g of nitrile-modified phenolic resin, 15g of CF@PVDF&PDA, 15g of calcium sulfate, 10g of alumina, 10g of barium sulfate, 10g of chromite, 5g of kaolin, 1g of carbon black, and 24g of calcium carbonate. Stir the above raw materials at 10000 rpm for 15 seconds to obtain a mixed powder. Adjust the density of the mixed powder to 1.8g / cm³. 3 Fill the mold; Step 8: Place the mold filled with the mixed powder into a flat vulcanizing machine for hot pressing and curing at a pressure of 5 MPa, a temperature of 180°C, and a time of 15 min to obtain a pre-cured friction material. Apply a pressure of 2 MPa to the pre-cured friction material using a fixture and place it in an oven for heat treatment. Hold at 110°C for 40 min, 130°C for 75 min, 150°C for 140 min, and 170°C for 55 min. Then cool to room temperature to obtain a PVDF & PDA interface modified carbon fiber reinforced resin-based friction material.
[0063] Comparative Example 1: Comparative Example 1 describes the preparation of a carbon fiber reinforced resin-based friction material using unmodified carbon fibers. The purpose is to compare its performance with that of a PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material. The specific steps include: Step 1: Pre-treat polyacrylonitrile-based carbon fibers by soaking the carbon fibers in acetone for 48 hours, washing them thoroughly with deionized water, and drying them at 80°C for 6 hours to obtain pre-treated carbon fibers. Step 2: Accurately weigh 15g of cashew nut shell oil-modified phenolic resin, 20g of pretreated carbon fiber, 15g of barium sulfate, 5g of alumina, 10g of barium sulfate, 10g of chromite, 1g of carbon black, and 24g of calcium carbonate. Stir the above raw materials at 10000 rpm for 15 seconds to obtain a mixed powder. The mixed powder is then sized to a density of 1.8g / cm³. 3 Fill the mold; Step 3: Place the mold filled with the mixed powder into a flat vulcanizing machine for hot pressing and curing at a pressure of 5.5 MPa, a temperature of 165°C, and a time of 13 min to obtain a pre-cured friction material. Apply a pressure of 1.5 MPa to the pre-cured friction material using a fixture and place it in an oven for heat treatment. Hold at 115°C for 35 min, 135°C for 70 min, 155°C for 130 min, and 175°C for 50 min. Then cool to room temperature to obtain a carbon fiber reinforced resin-based friction material.
[0064] Comparative Example 2: Comparative Example 2 describes the preparation of carbon fiber reinforced resin-based friction materials using PVDF single-coating modified carbon fibers. The purpose is to compare the performance with that of PVDF & PDA interface-modified carbon fiber reinforced resin-based friction materials, illustrating the role of the PDA coating at the interface. The specific steps include: Step 1: Pre-treat polyacrylonitrile-based carbon fibers by soaking the carbon fibers in acetone for 48 hours, washing them thoroughly with deionized water, and drying them at 80°C for 6 hours to obtain pre-treated carbon fibers. Step 2: Prepare 500 mL of 30% hydrogen peroxide solution, immerse 20 g of pretreated carbon fiber in the hydrogen peroxide solution for oxidation for 24 h, wash and filter with deionized water, and dry at 60 °C for 12 h to obtain oxidized carbon fiber. Step 3: Add 20g of PVDF to 480g of NMP organic solvent, and stir at 85℃ and 950rpm to fully dissolve the PVDF, resulting in 500g of PVDF solution. Step 4: Impregnate 20g of oxidized carbon fiber in 500g of PVDF solution and treat at 85℃ for 3.5h. Then squeeze out the excess solution, wash with deionized water, filter, and dry at 70℃ for 8h to obtain CF@PVDF. Step 5: Accurately weigh 15g cashew nut shell oil modified phenolic resin, 20g CF@PVDF, 15g barium sulfate, 5g alumina, 10g barium sulfate, 10g chromite, 1g carbon black, and 24g calcium carbonate. Stir the above raw materials at 10000rpm for 15s to obtain a mixed powder. Adjust the density of the mixed powder to 1.8g / cm³. 3 Fill the mold; Step 6: Place the mold filled with the mixed powder into a flat vulcanizing machine for hot pressing and curing at a pressure of 5.5 MPa, a temperature of 165°C, and a time of 13 min to obtain a pre-cured friction material. Apply a pressure of 1.5 MPa to the pre-cured friction material using a fixture and place it in an oven for heat treatment. Hold at 115°C for 35 min, 135°C for 70 min, 155°C for 130 min, and 175°C for 50 min. Then cool to room temperature to obtain a PVDF interface-modified carbon fiber reinforced resin-based friction material.
[0065] The relevant performance indicators of Examples 1-4 and Comparative Examples 1-2 were tested using the following methods: Damping performance: Following existing dynamic mechanical analysis methods in the art for testing damping performance, the test was conducted using a dynamic mechanical analyzer (model: Q800) according to ASTM D7028 standard, in a single cantilever beam mode. During the test, a periodic small-amplitude dynamic load was applied to the sample at room temperature, a frequency of 5 Hz, and a strain amplitude of 10 µm. The sample was a regular 35 × 12 × 3 mm block specimen.
[0066] Shear strength: Following existing methods in the art for testing shear strength, a computer-controlled electronic universal testing machine (model: CMT5304) was used to perform compression shear tests on the samples. The test mold consisted of an upper indenter, a base, and a sleeve. Pressure was applied to the upper indenter of the mold using the electronic universal testing machine at a loading rate of 0.2 mm / min. The samples were regular 10 mm × 10 mm × 10 mm block specimens, and the average value was calculated for each group of 5 specimens.
[0067] Tribological properties: The tribological properties were tested according to existing methods in the art. A scaled-down inertia tribological testing machine (model: MM-3000) was used to test the samples, equipped with an accelerometer (model: BWT61CL) and a high-precision sound level meter (model: GM1356). The spindle inertia was 0.1 kg·mm². 2 The braking cycle was 300 times. The mating material was C45E4 steel. The friction coefficient and wear rate were obtained at a braking pressure of 0.50 MPa and a speed of 2000 rpm. Since friction-induced vibration and noise are more prominent under low speed and heavy load, the vibration and noise levels were obtained at a braking pressure of 1 MPa and a speed of 300 rpm. The sample was a ring-shaped specimen with dimensions of Φ82.5 mm × 60.0 mm × 3 mm.
[0068] from Figure 1 As can be seen, in Comparative Example 1, the surface of the pretreated carbon fiber is relatively smooth and clean, with only some shallow grooves present.
[0069] Depend on Figure 2As can be seen in Comparative Example 2, after coating with a single PVDF layer, a distinct coating appeared on the surface of the carbon fiber. The distribution of F element on the surface was tested using EDS, and the results showed that the distribution of F element was consistent with the distribution of carbon fiber, and the F element came from PVDF.
[0070] Depend on Figure 3 As can be seen, in Example 1, a thin coating appears on the surface of the carbon fiber coated with PDA, and the distribution of N element is consistent with that of carbon fiber, with N coming from PDA.
[0071] Depend on Figure 4 As can be seen, in Example 1, the carbon fiber modified by PVDF and PDA double coating has a dense and thick surface coating, and the distribution of F and N elements is consistent with that of carbon fiber.
[0072] Depend on Figure 5 It can be seen that the surface of the unmodified carbon fiber in Comparative Example 1 is only at 3440 cm⁻¹ -1 1627cm -1 Stretching vibration peaks of OH and C=O appeared at 880 cm⁻¹, respectively. In Comparative Example 2, in addition to the aforementioned characteristic peaks, CF@PVDF also showed a series of characteristic peaks corresponding to PVDF, at 880 cm⁻¹. -1 The absorption peak at 1071 cm⁻¹ is caused by the vibration of -CH₂ and the rotation of -CF₂. -1 The absorption peak at 1185 cm⁻¹ is caused by the bending of CCC. -1 The absorption peak at 1404 cm⁻¹ is caused by the bending of -CF₂. -1 The absorption peak at 1671 cm⁻¹ is caused by the in-plane bending or shearing of -CH₂. In Example 1, for CF@PVDF&PDA, in addition to the characteristic absorption peak of PVDF mentioned above, there is also an absorption peak at 1671 cm⁻¹. -1 The NH bending vibration peak from PDA was also added at this point. The results show that the PVDF single coating in Comparative Example 2 and the PVDF&PDA double coating in Example 1 were both successfully coated on the carbon fiber surface.
[0073] The unmodified carbon fiber reinforced resin-based friction material prepared in Comparative Example 1 had a loss factor of 0.01592, a shear strength of 14.29 MPa, and a wear rate of 7.53 × 10⁻⁶. -8 cm 3 / J, the average amplitude of the friction-induced vibration is 0.462 m / s. 2 The noise equivalent sound level is 86.265 dB(A).
[0074] The PVDF single-coated modified carbon fiber reinforced resin-based friction material prepared in Comparative Example 2 had a loss factor of 0.01832, a shear strength of 12.83 MPa, and a wear rate of 3.59 × 10⁻⁶. -8 cm3 / J, the average amplitude of the friction-induced vibration is 0.421 m / s. 2 The noise equivalent sound level is 77.841 dB(A).
[0075] The PVDF & PDA dual-coated modified carbon fiber reinforced resin-based friction material prepared in Example 1 had a loss factor of 0.01847, a shear strength of 16.58 MPa, and a wear rate of 1.93 × 10⁻⁶. -8 cm 3 / J, the average amplitude of the friction-induced vibration is 0.380 m / s. 2 The noise equivalent sound level is 72.215 dB(A).
[0076] Combining Comparative Examples 1 and 2 with Example 1, it was found that PVDF at the carbon fiber interface effectively improved the damping performance of the friction material. Compared with the unmodified carbon fiber reinforced resin-based friction material in Comparative Example 1, the loss factor of the PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material in Example 1 increased from 0.01592 to 0.01847, an increase of 16.01%, indicating that PVDF used for fiber interface modification has a good effect on improving the material's damping capacity. The main reason is that there is a difference in the deformation capacity between carbon fiber and the matrix itself. After applying an external load, the interface bears greater stress, which is more conducive to utilizing the deformation capacity of the PVDF coating, thereby consuming vibration energy. Excellent damping performance helps the friction material dissipate vibration energy during friction, which is beneficial for suppressing vibration and noise during friction. However, although PVDF has excellent damping characteristics, due to the poor adhesion between PVDF and fiber, fiber debonding is prone to occur. Therefore, the shear strength of the PVDF single-coat interface-modified carbon fiber reinforced resin-based friction material in Comparative Example 2 decreased compared with Comparative Example 1. Furthermore, PDA was introduced as the bottom coating. PDA enhanced the bonding force between the fiber and the coating, thereby improving the interfacial bonding and allowing more load to be transferred to the fiber. Compared with Comparative Example 1, the shear strength of Example 1 increased from 14.29 MPa to 16.58 MPa. Good shear strength is beneficial for resisting alternating shear stress during friction.
[0077] from Figure 6It can be seen that the friction coefficient of the modified material decreases due to the lubricating properties of PVDF, with an average value around 0.33. Further calculations were made of the coefficient of friction variation (Cv(µ)) for different samples. The Cv(µ) for Comparative Example 1, Comparative Example 2, and Example 1 were 3.21%, 4.32%, and 2.27%, respectively. The coefficient of variation reflects the degree of fluctuation in the friction coefficient. The phenomenon in Comparative Example 2 is due to the weak interfacial bonding between the fiber matrix, leading to the peeling of the surface fibers during friction, thus increasing the fluctuation range of the friction coefficient. With PDA as the bottom coating, the fibers are less likely to be pulled out and peel off during friction; therefore, the friction coefficient curve of Example 1 shows relatively smaller fluctuations.
[0078] from Figure 7 As can be seen, due to the excellent lubricity and wear resistance of PVDF, the wear rates of Comparative Example 2, Example 1, and the mating couple were significantly improved. In particular, after PVDF & PDA dual-coating interface modification, the fiber-matrix interface bonding was strengthened, which facilitated greater dissipation of interfacial toughness and reduced fatigue wear. Simultaneously, wear caused by fiber pull-out was also reduced, resulting in a low wear rate. Compared to Comparative Example 1 and Comparative Example 2, the wear rate of Example 1 decreased by 74.3% and 46.2%, respectively. The damage to the mating couple caused by the modified friction material was also improved; compared to Comparative Example 1 and Comparative Example 2, the wear rate of the mating couple in Example 1 decreased by 71.0% and 36.3%, respectively.
[0079] In summary, Comparative Examples 1 and 2 maintained essentially the same formulation system as Example 1, differing only in the carbon fiber interface state. The comparative results further illustrate the dominant role of interface modification in material performance. Due to the influence of the PVDF & PDA dual-coating interface on the overall performance of the friction material, its excellent damping properties, shear resistance, and surface state resulted in a 17.4% and 9.7% reduction in vibration level during friction, and a 14.050 dB(A) and 5.626 dB(A) reduction in noise level, compared to Comparative Examples 1 and 2, respectively.
[0080] The PVDF & PDA dual-coated modified carbon fiber reinforced resin-based friction material prepared in Example 2 had a loss factor of 0.01902, a shear strength of 17.94 MPa, and a wear rate of 1.63 × 10⁻⁶. -8 cm 3 / J, the average amplitude of the friction-induced vibration is 0.327 m / s. 2 The noise equivalent sound level is 70.920 dB(A).
[0081] The PVDF & PDA dual-coated modified carbon fiber reinforced resin-based friction material prepared in Example 3 had a loss factor of 0.01829, a shear strength of 16.05 MPa, and a wear rate of 2.25 × 10⁻⁶. -8 cm 3 / J, the average amplitude of the friction-induced vibration is 0.389 m / s. 2 The noise equivalent sound level is 73.863 dB(A).
[0082] The PVDF & PDA dual-coated modified carbon fiber reinforced resin-based friction material prepared in Example 4 had a loss factor of 0.01798, a shear strength of 15.64 MPa, and a wear rate of 2.52 × 10⁻⁶. -8 cm 3 / J, the average amplitude of the friction-induced vibration is 0.403 m / s. 2 The noise equivalent sound level is 75.687 dB(A).
[0083] This demonstrates that the effectiveness and applicability of the interface modification method of the present invention have been verified in various formulation systems.
[0084] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material, characterized in that, By weight percentage, it includes: 10-20% thermosetting phenolic resin, 15-25% PVDF & PDA double-coated modified carbon fiber, and 55-75% filler.
2. The PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 1, characterized in that, Thermosetting phenolic resins include boron-modified phenolic resins, cashew nut shell oil-modified phenolic resins, nitrile-modified phenolic resins, and oil-modified phenolic resins. PVDF&PDA double-coated modified carbon fibers include polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, and viscose-based carbon fibers modified with PVDF&PDA double coating. The filler is one or more of the following: alumina, barium sulfate, chromite, calcium carbonate, carbon black, graphite, fluorite powder, and kaolin.
3. A method for preparing the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to any one of claims 1 to 2, characterized in that, include: The pretreated carbon fiber was immersed in hydrogen peroxide solution for oxidation treatment, and then washed with deionized water, filtered and dried to obtain oxidized carbon fiber. Dilute hydrochloric acid solution was added dropwise to an aqueous solution of tris(hydroxymethyl)aminomethane to adjust the pH, resulting in a Tris-HCl buffer solution. Dopamine was then added to the Tris-HCl buffer solution to obtain an aqueous solution of DA. Oxidized carbon fibers were immersed in a DA aqueous solution to undergo a self-polymerization reaction. After washing with deionized water, filtering, and drying, PDA single-coated modified carbon fibers were obtained. Polyvinylidene fluoride was added to 1-methyl-2-pyrrolidone organic solvent and dissolved completely under heating and stirring conditions to obtain a PVDF solution. PDA-coated modified carbon fiber is immersed in PVDF solution for coating, so that PVDF forms a coating layer on the surface of the carbon fiber. After washing with deionized water, filtering and drying, PVDF&PDA double-coated modified carbon fiber is obtained. Thermosetting phenolic resin, PVDF & PDA double-coated modified carbon fiber and filler are mixed, filled into a mold, and then subjected to hot pressing curing and heat treatment to obtain PVDF & PDA interface modified carbon fiber reinforced resin-based friction material.
4. The preparation method of the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 3, characterized in that, The pretreatment process for carbon fiber is as follows: Soak carbon fibers in acetone for 24-48 hours, wash thoroughly with deionized water and dry at 80-100℃ for 4-6 hours.
5. The preparation method of the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 3, characterized in that, The mass fraction of hydrogen peroxide solution is 25%~35%; The mass-to-volume ratio of the pretreated carbon fiber to the hydrogen peroxide solution is 1:20~30; The oxidation treatment time is 20~28h.
6. The method for preparing the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 3, characterized in that, The pH of the Tris-HCl buffer solution is 8.5; The mass concentration of tris(hydroxymethyl)aminomethane aqueous solution is 1~2 g / L; The concentration of the dilute hydrochloric acid solution is 0.01~0.02 mmol / L; The mass concentration of dopamine aqueous solution is 3~4 g / L; The mass-to-volume ratio of oxidized carbon fiber to DA aqueous solution is 1:100~120; The self-polymerization reaction time is 24~36h, and the temperature is room temperature.
7. The preparation method of the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 3, characterized in that, The mass ratio of polyvinylidene fluoride to 1-methyl-2-pyrrolidone is 1:19~39; The heating temperature is 80~100℃; The stirring speed is 800~1000 r / min, and the stirring time is 10~15 min; The mass ratio of PDA single-coated modified carbon fiber to PVDF solution is 1:20~30; The coating time is 3-4 hours, and the temperature is 80-100℃.
8. The method for preparing the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 3, characterized in that, The drying temperature for oxidized carbon fiber, PDA single-coated modified carbon fiber, and PVDF & PDA interface modified carbon fiber is 60~80℃, and the drying time is 6~12h.
9. The method for preparing the PVDF&PDA interface-modified carbon fiber reinforced resin-based friction material according to claim 3, characterized in that, The pressure for hot-press curing is 5~10MPa, the temperature is 160~185℃, and the time is 10~15min; The heat treatment pressure is 1~2 MPa, and the gradient heating process is as follows: heat to 110~120℃ and hold for 30~40 min, heat to 130~140℃ and hold for 65~75 min, heat to 150~160℃ and hold for 120~140 min, heat to 170~180℃ and hold for 45~55 min, and then cool to room temperature.
10. The application of the PVDF & PDA interface-modified carbon fiber reinforced resin-based friction material according to any one of claims 1 to 2 in a friction braking device.